Spectroscopy of substituted benzene molecules - Andrejeva, Anna (2016)
Consistent assignment of vibrational motions across substituted benzene derivatives is a long-standing desire amongst spectroscopists. In this thesis, the S1 electronic states of monohalosubstituted benzene molecules and their deuterated isotopologues are investigated, using resonance enhanced multiphoton ionisation spectroscopy. The observed vibrational bands are assigned using the Mi nomenclature proposed by Gardner and Wright where ring localised vibrations having the same atomic motion are given the same label, allowing straightforward comparisons of vibrational motions across monosubstituted benzene molecules to be achieved. Detailed investigation showed that it would not be possible to apply the same Mi nomenclature labels to the para disubstutited benzene derivatives owing to the different vibrational motions of mono- and disubstituted benzene molecules. As a consequence a new nomenclature, Di, for labelling the vibrational motions of para disubstituted benzene molecules is proposed in this work. The Di labelling scheme is based on the vibrations of the para difluorobenzene molecule. S0 state vibrations of symmetric and asymmetric para dihalobenzene species, para fluorotoluene and para xylene are studied in detail, showing that the ring localised vibrational motions of para disubstituted benzene species are being described by the same label.